How to build a rapport (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. What do you gain when you establish rapport? Your teams will work better, you'll encourage people to follow you, people will commit to you in meaningful ways, and you'll be a person of influence. In this track, you'll learn how to create rapport with the people you meet. You'll see how charismatic and empathetic people create rapport in three ways: Active listening Body language Choice of words Learning Objectives Learn how to build rapport Learn active listening Learn how to change your body language to encourage empathy Learn how to choose supportive vocabulary.